A novel hypothesis on the biochemical role of the Drosophila Yellow protein. - Drapeau, M.D. (Biochemical and Biophysical Research Communications, 2003)
In Drosophila melanogaster, the protein product of the yellow gene is necessary for normal pigmentation and male sexual behavior. Although one of the best characterized loci from a genetic standpoint, the function of the Yellow protein in the development of either phenotype is unknown. Here I propose that Yellow acts as a growth factor- or hormone-like molecule in the development of pigmentation and sexual behavior, and discuss the consistency of this theory with experimental observations in flies and humans.